2013
DOI: 10.1038/pr.2013.249
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of the newborn mouse brain after hypoxia–reoxygenation: hyperoxic reoxygenation induces inflammatory and energy failure responsive genes

Abstract: Background: Supplemental oxygen used during resuscitation can be detrimental to the newborn brain. The aim was to determine how different oxygen therapies affect gene transcription in a hypoxia-reoxygenation model. Methods: C57BL/6 mice (n = 56), postnatal day 7, were randomized either to 120 min of hypoxia 8% O 2 followed by 30 min of reoxygenation with 21, 40, 60, or 100% O 2 , or to normoxia followed by 30 min of 21 or 100% O 2 . Affymetrix 750k expression array was applied with RT-PCR used for validation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…Perez-Polo and coworkers found a stronger inflammatory response after hyperoxic reoxygenation following HI in rats (24,25). We also found increased protein concentration of CCL12, a proinflammatory chemokine, after hyperoxic reoxygenation, consistent with our recent reports of increased Ccl12 expression in the eye and brain of neonatal mice after hyperoxic reoxygenation (17,26). Mojsilovic-Petrovic et al (27) found increased expression of Ccl12 in astrocyte cultures from P7 mice after hypoxia alone.…”
Section: Igf1rsupporting
confidence: 90%
See 4 more Smart Citations
“…Perez-Polo and coworkers found a stronger inflammatory response after hyperoxic reoxygenation following HI in rats (24,25). We also found increased protein concentration of CCL12, a proinflammatory chemokine, after hyperoxic reoxygenation, consistent with our recent reports of increased Ccl12 expression in the eye and brain of neonatal mice after hyperoxic reoxygenation (17,26). Mojsilovic-Petrovic et al (27) found increased expression of Ccl12 in astrocyte cultures from P7 mice after hypoxia alone.…”
Section: Igf1rsupporting
confidence: 90%
“…In our transcriptome profiling study, we have recently shown that hyperoxic reoxygenation induced increased expression of inflammatory genes in the neonatal mice brain (17). Previously, we have reported a dose dependent increase in markers of …”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations